Analysis of bacteriocins of lactic acid bacteria isolated from fermentation of rebon shrimp (Acetes sp.) in South Sorong, Indonesia as antibacterial agents - SUKMAWATI SUKMAWATI; SIPRIYADI SIPRIYADI; MELDA YUNITA; NURUL KUSUMA DEWI; ERIN D. NOYA (Society for Indonesian Biodiversity, 2022)
Abstract. Sukmawati S, Sipriyadi, Yunita M, Dewi NK, Noya ED. 2022. Analysis of bacteriocins of lactic acid bacteria isolated from fermentation of rebon shrimp (Acetes sp.) in South Sorong, Indonesia as antibacterial agents. Biodiversitas 23: xxxx. Bacteriocins are protein compounds that are often used as biopreservative agents due to their antibacterial effects against various types of pathogenic bacteria. Bacteriocins are used as food additives that can control the growth of spoilage bacteria in food. Bacteriocins can be obtained from Lactic Acid Bacteria (LAB) and are generally isolated from fermentation products, such as rebon shrimp fermentation. The objective of this study was to analyze the activity of bacteriocins isolated by fermented rebon shrimp in South Sorong as antibacterials. The method used in this study is a descriptive study by describing the ability of bacteriocins to inhibit pathogenic bacteria (Staphylococcus aureus, Escherichia coli, and Salmonella typhimurium). The results showed that of the seven bacteriocin samples obtained from the fermented rebon shrimp paste and acidic shrimp paste were able to inhibit the growth of pathogenic bacteria (S. aureus, E. coli, and S. typhimurium). The sensitivity test of bacteriocin to protease enzymes and its activity against pathogenic bacteria showed that bacteriocins derived from LAB were not sensitive to proteinase-K. The test results of the effect of temperature on bacteriocins and their activity against pathogenic bacteria showed that these bacteriocins were stable at high temperatures, normal temperatures and freezing temperatures. The test results of the effect of pH on bacteriocin activity on pathogenic bacteria showed that bacteriocins were stable in a wide pH range including pH 2, pH 3, pH 4, and pH 5; potassium phosphate buffer with pH 6, 7, and 8; and glycine buffer with pH 9, 10, and 11. Meanwhile, The test results of the effect of NaCl on bacteriocin activity on pathogenic bacteria showed that the bacteriocin sample was not affected by the administration of NaCl. Thus it can be stated that the seven samples had a great ability to inhibit the growth of pathogenic bacteria dan it can be further developed as the basis of natural food preservatives.